2019
DOI: 10.1177/0734282919862144
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration of Mokken Scale Analysis Methods Applied to Cognitive Test Validation Using the Egyptian WAIS-IV

Abstract: The fourth edition of the Wechsler Adult Intelligence Scale (WAIS-IV) has been used extensively for assessing adult intelligence. This study uses Mokken scale analysis to investigate the psychometric proprieties of WAIS-IV subtests adapted for the Egyptian population in a sample of 250 adults between 18 and 25 years of age. The monotone homogeneity model and the double monotonicity model were consistent with the subtest data. The items of all subtests except Matrix Reasoning, Information, Similarities, and Voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Consequently, our results, while preliminary, suggest that WAIS-IV items need to be re-sequenced for the Arabic-speaking population in order to yield more accurate scores. This is consistent with the conclusion reached by Abdelhamid et al [ 23 ] and Suwartono et al [ 47 ], who likewise suggested that the item order proposed in the U.S. WAIS-IV manual was inappropriate for, respectively, the Egyptian and the Indonesian population. However, it is also necessary to take into account the different characteristics of the samples used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, our results, while preliminary, suggest that WAIS-IV items need to be re-sequenced for the Arabic-speaking population in order to yield more accurate scores. This is consistent with the conclusion reached by Abdelhamid et al [ 23 ] and Suwartono et al [ 47 ], who likewise suggested that the item order proposed in the U.S. WAIS-IV manual was inappropriate for, respectively, the Egyptian and the Indonesian population. However, it is also necessary to take into account the different characteristics of the samples used.…”
Section: Discussionsupporting
confidence: 92%
“…The WAIS-IV used in the present study was the version for Arabic speakers, adapted and validated by Abdelhamid et al [ 10 , 23 ]. It consists of 10 core subtests (Block Design, Matrix Reasoning, Visual Puzzles, Digit Span, Arithmetic, Similarities, Vocabulary, Information, Symbol Search, and Coding) that yield scores on four factors, as well as a full IQ score.…”
Section: Methodsmentioning
confidence: 99%
“…Our results established that the empirical data were consistent with a monotone homogeneity model, and many of the items discriminated well, though about twelve items (H j < 0.30) were identified as misfits when measured by scalability coefficient; all of the item pairs (H ij ) were positive. This lends credence to the work of [7,26] that the sum of the test score is a better indicator of the latent trait. This can be used to order the students on the latent continuum trait.…”
Section: Discussionsupporting
confidence: 73%
“…In practice, [25] recommends the following rule of thumb for the interpretation of the scale: scale values of H < 0.30 are not considered to be unidimensional, values of 0.30 ≤ H < 0.40 are a weak scale that is unidimensional but not strong, values of 0.40 ≤ H < 0.50 are of medium strength, and only when H > 0.50 is the scale regarded as strong. Greater H values indicate that the slope of the item characteristic curves (ICCs) tend to be steeper, which implies that the items discriminate better among different latent traits θ [26].…”
Section: Introductionmentioning
confidence: 99%